Case Report: The combination of upadacitinib and adalimumab in the treatment of refractory ankylosing spondylitis - Wu, Jiajia; Wang, Weiwei; Cheng, Xi; Song, You; Yuan, Xujing; Du, Rong (Frontiers in Immunology, 2025)
Ankylosing spondylitis (AS) is a chronic inflammatory disease primarily affecting the axial skeleton and peripheral joints, with potential extra-articular involvement. This study documents the first successful application of upadacitinib-adalimumab combination therapy in refractory AS (disease duration >20 years). Following sequential treatment failures with NSAIDs, TNF inhibitors (adalimumab/etanercept), IL-17 inhibitors (secukinumab), and JAK inhibitors (tofacitinib followed by upadacitinib monotherapy) amidst persistently high disease activity (BASDAI >4 or ASDAS-CRP >2.1), this mechanistically-driven dual-target approach leveraging synergistic JAK-TNF pathway inhibition achieved significant clinical improvement within six months: inflammatory markers decreased substantially (C-reactive protein from 64.6 mg/L to 7.59 mg/L; erythrocyte sedimentation rate from 56 mm/h to 5 mm/h), accompanied by marked reductions in disease activity scores (ASDAS-CRP from 3.9 to 1.77; BASDAI from 3.8 to 1.4). Crucially, rigorous surveillance exceeding 12 months detected no severe adverse events including serious infections or major adverse cardiovascular events. This case establishes targeted combination therapy with intensive safety monitoring as a viable option for multi-drug refractory AS, warranting further validation studies.